(untitled) (SAARC Journal of Agriculture, 2015)
High heritability coupled with high to moderate phenotypic and genotypic coefficient of variation and genetic advance as per cent of mean was recorded for grain yield per plant, plant height, test weight, fertile spikelet per panicle, total grains per panicle and number of effective tillers per plant. Positive and significant association were observed for days to 50 per cent flowering, days to maturity, plant height, panicle length, fertile spikelet per panicle, total grains per panicle and spikelet fertility with grain yield per plant at both genotypic and phenotypic level, while highest positive direct effect on grain yield was recorded by fertile spikelet per panicle, total number of grains per panicle, plant height and days to 50% flowering. Based on ten quantitative traits the accessions were clustered into seven groups, the cluster III contained highest 14 accessions, followed by clusters I comprised 11 accessions and cluster VI, VII, V, IV and II have 9, 8, 7, 6 and 5 accessions, respectively. The first four principal components accounted for 77.13% of total variation of all the traits. DOI: http://dx.doi.org/10.3329/sja.v12i2.21915 SAARC J. Agri., 12(2): 40-51 (2014)